Hubungan Framingham Risk Score dengan Derajat TIMI Risk Score pada Pasien Infark Miokard Akut dengan Elevasi Segmen ST di RSUP Prof. Dr. R. D. Kandou Periode Januariâ€“September 2018 - Alitu, Moh. A. R.; Jim, Edmond L.; Joseph, Victor F. (e-CliniC, 2018)
Abstract: Myocardial infarction (MI) is one of the main manifestations of coronary heart diseases. ST segment elevation myocardial infarction (STEMI) is a symptomatic clinical syndrome characterized by myocardial ischemia associated with persistent ST segment elevation. The Framingham risk score (FRS) is designed to predict the risk of death due to coronary heart disease and myocardial infarction meanwhile the TIMI risk score is used as a tool to determine the mortality risk of STEMI patients. This study was aimed to determine the relationship between the FRS and the degree of TIMI risk score in STEMI patients at Prof. Dr. R. D. Kandou Hospital Manado. This was a retrospective analytical study. Samples were patients diagnosed as STEMI at Prof. Dr. R. D. Kandou Hospital Manado from January to September 2018. There were 93 patients obtained by using total sampling. The Pearson correlation test of the relationship between the FRS and the degree of TIMI risk score in STEMI patients obtained an r of 0.097 with the P value of 0.177. Conclusion: There was no relationship between the Framingham risk score and the TIMI risk score among IMA-EST patients.Keywords: myocardial infarction, Framingham risk score, TIMI risk score, STEMIÂ Abstrak: Infark miokard adalah salah satu manifestasi utama penyakit jantung koroner (PJK). Infark miokard akut dengan elevasi segmen ST (IMA-EST) adalah sindrom klinis dengan gejala karakteristik iskemia miokard yang berhubungan dengan elevasi segmen ST persisten. Framingham risk score (FRS) dirancang untuk memrediksi risiko kematian karena PJK dan infark miokard. TIMI risk score digunakan sebagai alat untuk menentukan risiko mortalitas pasien IMA-EST. Penelitian ini bertujuan untuk mengetahui hubungan FRS dengan derajat TIMI risk score pada pasien IMA-EST di RSUP Prof. Dr. R. D. Kandou. Jenis penelitian ialah analitik retrospektif. Sampel penelitian ialah pasien IMA-EST di RSUP Prof. Dr. R. D. Kandou Manado periode Januari-September 2018 sebanyak 93 pasien diambil dengan total sampling. Hasil uji korelasi Pearson terhadap hubungan antara FRS dan TIMI risk score pada pasien IMA-EST mendapatkan r=0,097 dengan nilai P=0,177. Simpulan: Tidak terdapat hubungan antara Framingham risk score dan TIMI risk score pada pasien IMA-EST.Kata kunci: infark miokard, Framingham risk score, TIMI risk score, IMA-EST